STRENGTHENING INTERNATIONAL LAW AS A GUARANTEE FOR HIGH SEAS FISHERIES CONSERVATION - Tarigan, Muhammad Insan; Tirtamulia, Tjondro (Asosiasi Pembina Hukum Lingkungan Indonesia (PHLI), 2020)
High seas is one of the ocean areas beyond of national jurisdiction. The implication of that definition made high seas turn into a free access to all states. One of freedom of high seas had known of yore is freedom of fishing, as if high seas fishery is inexhaustible. However, technological advances in fishing gear and people demand towards ocean fish causing overfishing and Illegal, Unreported, and Unregulated (IUU) Fishing are unavoided. Living resources and the environment of the high seas are more susceptible due to weak regulation on the UNCLOS 1982 which are cooperation for conservation and no restriction on exploitation. With that regard, international law-making concerning management and conservation concept based on the high seas fisheries sustainability need to be done. This article was written by normative research conducted with library studies by maximizing data in any journals and books. The concept of Marine Protected Areas (MPAs) and the establishment of Conservation Zone in the high seas is considered to have potential for fisheries management development that guarantee the sustainability of diversity high seas fisheries.